2015
DOI: 10.7589/2014-08-198
|View full text |Cite
|
Sign up to set email alerts
|

ORAL SHEDDING OF MARBURG VIRUS IN EXPERIMENTALLY INFECTED EGYPTIAN FRUIT BATS (ROUSETTUS AEGYPTIACUS)

Abstract: Marburg virus (Marburg marburgvirus; MARV) causes sporadic outbreaks of Marburg hemorrhagic fever (MHF) in Africa. The Egyptian fruit bat (Rousettus aegyptiacus) has been identified as a natural reservoir based most-recently on the repeated isolation of MARV directly from bats caught at two locations in southwestern Uganda where miners and tourists separately contracted MHF from 2007–08. Despite learning much about the ecology of MARV through extensive field investigations, there remained unanswered questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
238
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(259 citation statements)
references
References 16 publications
15
238
5
1
Order By: Relevance
“…gorillas) (Leroy et al 2004). Recent experimental studies have shown that Marburg virus can be excreted in bat saliva, answering important questions about its potential zoonotic spread via the oral route (Amman et al 2014a). It has been postulated that bats and gorillas may share Ebola virus through contact at shared fruit resources, but this has not been verified and additional research is needed to better understand the ecological connections between bats and other mammal hosts in the transmission of these diseases (Groseth et al 2007;Olival and Hayman 2014).…”
Section: Food-borne Zoonotic Disease Risk From Pteropodid Batsmentioning
confidence: 99%
“…gorillas) (Leroy et al 2004). Recent experimental studies have shown that Marburg virus can be excreted in bat saliva, answering important questions about its potential zoonotic spread via the oral route (Amman et al 2014a). It has been postulated that bats and gorillas may share Ebola virus through contact at shared fruit resources, but this has not been verified and additional research is needed to better understand the ecological connections between bats and other mammal hosts in the transmission of these diseases (Groseth et al 2007;Olival and Hayman 2014).…”
Section: Food-borne Zoonotic Disease Risk From Pteropodid Batsmentioning
confidence: 99%
“…A second study by Amman et al . found that bats subcutaneously inoculated with a low-passage, bat-derived MARV strain shed virus in their oral secretions up to 11 days following infection and led to the hypothesis that the virus may be horizontally transmitted between bats through direct and/or indirect contact with infectious oral secretions or biting 29 . To investigate the mechanisms of bat-to-bat MARV transmission, a third study by Paweska et al .…”
Section: Natural History Of Marv Infection In R Aegyptiacusmentioning
confidence: 99%
“…Genome sequences of MARV isolated from bats closely matched those isolated from miners during this epidemic, indicating that common Egyptian fruit bats represent major natural reservoir and source of Marburg virus with potential for spillover into humans. Despite the isolation of MARV from naturally infected Egyptian fruit bats captured in the Kitaka cave near Ibanda, in Western Uganda ) and the python cave in the Queen Elisabeth National Park, Uganda (Amman et al, 2014), experimental inoculation of R. aegyptiacus with MARV were conducted and showed that the species is a natural reservoir host for MARV and demonstrated routes of viral shedding via rectal and oral routes capable of infecting humans and other animals (Amman et al, 2015). While the Marburgviruses exhibit high overall genetic diversity (up to 22%), only 6.8% nucleotide difference was found between the West African Angolan viruses and the majority of East African viruses, suggesting that the virus reservoir species in these regions are not substantially distinct.…”
Section: The Reservoir Searchmentioning
confidence: 99%